Kajian Sistematis: Perkembangan Sistem Pembayaran Kapitasi Berbasis Penyesuaian Risiko di Berbagai Negara - Agustina, Aulia; Hidayat, Budi (Jurnal Ekonomi Kesehatan Indonesia, 2021)
Capitation is a payment method to primary health care providers. The application of capitation without considering risk adjustment could have a negative impact. There are several models of risk adjustment capitation payments. This study aims to review the development of the capitation payment system with risk adjustment for primary care in several countries. This study used the PRISMA method and got the articles from three online databases, namely Pubmed, EBSCOhost Medline, and Scopus. A total of 212 articles were collected, and 7 articles meet the criteria for further review. The review focuses on the risk-adjusted capitation payment system model. The results obtained that the risk-adjusted capitation payment system model is vary from simple to complex. The most frequently used risk factors were age and gender. The risk-adjusted capitation payment system model continues to develop, it is important to carry out periodic updates and adjustments. Various benefit from the implementation of the risk-adjusted capitation payment system model can be a reference for countries to get an appropriate risk-adjusted capitation policy formulation to be applied which proper to the conditions of each country